The disengagement of visual attention in Alzheimer's disease: a longitudinal eye-tracking study - Crawford, Trevor J. (Frontiers in Aging Neuroscience, 2015)
Introduction Eye tracking provides a convenient and promising biological marker of cognitive impairment in patients with neurodegenerative disease. Here we report a longitudinal study of saccadic eye movements in a sample of patients with dementia and elderly control participants who were assessed at start of the study and followed up 12 months later. Methods Eye movements were measured in the standard gap and overlap paradigms, to examine the longitudinal trends in the ability to disengage attention from a visual target. Results Overall patients with dementia had slower reaction times than the control group. However, after 12 months, both groups showed faster and comparable reductions in reaction times to the gap, compared to the overlap stimulus. Interestingly, there was a general improvement for both groups with more accurately directed saccades and speeding of reaction times after 12 months. Conclusions These findings point to the value of longer-term studies and follow-up assessment to ascertain the effects of dementia on oculomotor control.